Piano di uguaglianza di genere dell'Università degli Studi di Cagliari - University of Cagliari (UNICApress, 2020)
Through the adoption of the Gender Equality Plan, the University of Cagliari proposes itself as a strategic agent for the promotion of the European founding principle of gender equality, in its dual capacity as a place of socialization aimed at combating inequalities and applying the equity principles of substantive citizenship, and as a work organization characterized by diversities that can translate into the risk of inequalities in the distribution of positions and progression along professional paths. Indeed, the way scientific knowledge is generated is not disconnected from the overall structural system, which reproduces gender inequalities within research organizations. Research activity that is not free of gender stereotypes can fuel discrimination and limit equal opportunity within the organizations themselves. The undergraduate and postgraduate research and education sector has a distinctive educational mission, necessitating specific actions to overcome gender gaps. Gender Equality Plans fit into this view as key tools for generating structural changes in educational organizations and achieving the bridging of gender gaps. UNICA's Gender Equality Plan was developed under the Horizon 2020 project SUPERA - Supporting the promotion of equality in research and academia (grant agreement no. 787829 ). More information is available at www.superaproject.eu.